2015
DOI: 10.1111/petr.12636
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prophylactic use of intravenous immunoglobulin versus Pentaglobin® in pediatric patients after hematopoietic stem cell transplantation

Abstract: There are few studies evaluating the use of IgM-enriched IVIG (Pentaglobin(®) ) in HSCT recipients. This study aimed to compare the efficacy of prophylactic use of IVIG versus prophylactic use of Pentaglobin(®) within the first 100 days after allogeneic HSCT. We performed a prospective, randomized study of the use of prophylactic IVIG versus prophylactic use of Pentaglobin(®) in patients after allogeneic HSCT. The first dose of IVIG or Pentaglobin(®) was given before conditioning regimen and after transplant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…More recently, a prospective, randomized study in pediatric allo-HSCT compared the use of prophylactic i.v. polyclonal Ig with IgM-and IgA-enriched preparations given before conditioning and until engraftment, and found no significant differences between the 2 approaches [36]. Based on those data and our present results, we speculate that the impact of IgM-and IgAenriched Ig prophylactic administration on infection control might be not relevant when given without considering endogenous IgM and IgA levels.…”
Section: Figuresupporting
confidence: 61%
“…More recently, a prospective, randomized study in pediatric allo-HSCT compared the use of prophylactic i.v. polyclonal Ig with IgM-and IgA-enriched preparations given before conditioning and until engraftment, and found no significant differences between the 2 approaches [36]. Based on those data and our present results, we speculate that the impact of IgM-and IgAenriched Ig prophylactic administration on infection control might be not relevant when given without considering endogenous IgM and IgA levels.…”
Section: Figuresupporting
confidence: 61%
“…Among the included RCTs, 22 studies enrolled patients undergoing allogeneic HSCT (n = 3329), 43‐64 four (n = 435) enrolled patients undergoing either allogeneic or autologous HSCT, and one (n = 170) strictly enrolled patients undergoing autologous HSCT . Twelve RCTs (n = 2066) compared polyvalent IVIG to no treatment, nine compared CMVIG to no treatment (n = 619), two (n = 950) compared two different doses of IVIG, two (n = 177) compared polyvalent IVIG to CMVIG, one (n = 63) compared immunoglobulin M–enriched IVIG to no treatment, and one (n = 59) compared immunoglobulin M–enriched IVIG to polyvalent IVIG . No study used SCIG.…”
Section: Resultsmentioning
confidence: 99%
“…Availability of outcomes varied notably across trials. Eighteen studies (n = 2,553) reported overall survival, five (n = 443) reported transplant‐related mortality, 12 (n = 1,070) reported CMV infections, nine (n = 991) reported CMV diseases, 14 (n = 1,897) reported acute GVHD, seven (n = 551) reported chronic GVHD, five (n = 855) reported VOD, 11 (n = 2309) reported relapse, and 10 (n = 1699) reported interstitial pneumonitis. There were 12 studies that reported non‐CMV infections.…”
Section: Resultsmentioning
confidence: 99%
“…The only study previously reported for the pediatric cohort, which compared intravenous immunoglobulin prophylactic use to Pentaglobin ® , was administered to patients within 100 days after allogeneic HSCT. This study showed no differences between two groups concerning neutropenia, number of hospitalization days, total days of fever, number of consecutive detected infectious events, acute GVHD onset, VOD onset, and side effects [24].…”
Section: Discussionmentioning
confidence: 52%